2013
DOI: 10.1016/j.concog.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mindfulness meditation on time perception

Abstract: Research has increasingly focussed on the benefits of meditation in everyday life and performance. Mindfulness in particular improves attention, working memory capacity, and reading comprehension. Given its emphasis on moment-to-moment awareness, we hypothesised that mindfulness meditation would alter time perception. Using a within-subjects design, participants carried out a temporal bisection task, where several probe durations are compared to "short" and "long" standards. Following this, participants either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 36 publications
4
71
3
3
Order By: Relevance
“…Likewise, the subject's perception of the time elapsed in mental silence is subjective and likely an imprecise measure of the time elapsed based on a potentially very different ''mental" clock under a meditative state. Time perception has been suggested to be different in altered states of consciousness which would include meditation (Kramer et al, 2013). Nonetheless, meditators describe that the process to establish mental silence is normally slow because it takes time to reduce the random flow of uncontrolled thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the subject's perception of the time elapsed in mental silence is subjective and likely an imprecise measure of the time elapsed based on a potentially very different ''mental" clock under a meditative state. Time perception has been suggested to be different in altered states of consciousness which would include meditation (Kramer et al, 2013). Nonetheless, meditators describe that the process to establish mental silence is normally slow because it takes time to reduce the random flow of uncontrolled thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of meditation has been shown to develop individuals' awareness, defined as an individual ability to voluntarily orient attention toward specific ongoing information (internal-oriented attention). Using a temporal bisection task, Kramer, Weger, and Sharma (2013) recently showed that the practice of a 10-min mindfulness exercise lengthened the perception of time in participants who had no prior experience of meditation. In their study, the participants were initially presented with a short (S) (0.4 s) and a long standard duration (L) (1.6 s).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis is therefore that attention-related mechanisms account for the effects of meditation on the perception of time. To further test this hypothesis, we decided to examine the effect of a mindfulness exercise on the perception of time in a bisection task with longer durations (S = 4 s) than those used by Kramer et al (2013) and whose processing requires a higher level of attention. In addition, we used a difficult temporal discrimination task, with a small ratio between S and L of 2:3 (S = 4, L = 6 s) as well as an easier temporal discrimination task with a larger ratio of 1:2 (S = 4, L = 8 s).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that 'there is not an abstract knower of an experience that is separated from the experience itself' but instead one 'is at one with the experience' [31]. This form of being in the present brings with it a number of beneits, such as improving certain cognitive capacities [32,33], including the memory of work [34,35] and atentional processes [36,37], as well as increasing the cognitive and emotional lexibility of individuals [38]. It also results in a strategy of emotional regulation [30], which demonstrates efectiveness in the reduction of symptomatology [39], and an increase in positive mood states [40] and in psychological well-being [41].…”
Section: Change In Relation To Our Experiencementioning
confidence: 99%